Kolloquien im Wintersemester 2021/2022 - Reuß, Philipp (Universitätsverlag Göttingen, 2023)
The second volume of the "Göttingen Colloquia on the Digitalisation of Civil Procedure" contains the written presentations of the speakers of the three Friday Colloquia held in winter term 2021-22. The first colloquium was dedicated to the prospects and limits of the use of artificial intelligence in civil procedure under the heading "Robo Judge." The conference proceedings contain the respective contribution written by Prof. Dr. Thomas Riehm. The second colloquium dealt with "Digitalisation in Mass Proceedings", with the contributions of Prof. Dr. Caroline Meller-Hannich, Dr. Annekathrin Schmoll, Anna Katharina Zitt and Dr. Christopher Unseld. The third colloquium dealt with the hitherto hardly discussed topic of "Digital Hearings of Guardians and Guardians-to-be." This conference volume contains the contributions by Prof. Dr. Anika Gomille, Prof. Dr. Christian Gomille and Bernhard Klasen. In addition, the conference proceedings trace the sometimes controversial and lively discussions in small conference reports.